Impact of Social Deviation on Adolescents in Education - Hilal, Shekiba (Journal of Social Sciences - Kabul University, 2022)
Deviation refers to behavior that has a negative aspect. Deviation is found in different forms in every society. All societies, whether Western industrial societies or Eastern societies, have cultures, laws, and regulations which violation of that can cause anger, hatred, and opposition of the people of that society. Social deviations have diverse effects on adolescents, but one of its major effects is on adolescent’s education which is the subject of this article. The review method is used in this article and written using the opinions of thinkers and experts in this field. The main purpose is to increase the awareness of professors on impact of social deviations on the education of adolescents. The results show that recognizing the impact of social deviations on adolescents' education causes adolescents to become leaders themselves and overcome social deviations through education through diligence and hard work in education overcome the effects of social deviation and learn appropriate ways in their lives.